Semi-supervised learning - Chapelle, Olivier; Schölkopf, Bernhard; Zien, Alexander (Adaptive computation and machine learning., 2006)
A comprehensive review of an area of machine learning that deals with the use of unlabeled data in classification problems, this text looks at state-of-the-art algorithms, applications benchmark experiments, and directions for future research.